Resistance and Adaptation of Islamic Education in the Discourse of Islamic Ideology Language: A Socio-Historical Study of Old Order and New Order Politics: Resistensi dan Adaptasi Pendidikan Islam dalam Wacana Bahasa Ideologi Islam: Kajian Sosio-Historis Politik Orde Lama dan Orde Baru - Aldi, Muhammad; Supriyatno, Triyo; Trinova, Zulvia; Muslimin, Imam (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Islamic education in Indonesia experienced significant dynamics under pressure and interaction with state power during the Old and New Order periods. Purpose: This research aims to examine the forms of resistance and adaptation of Islamic education in the socio-political context of the Old and New Order eras. Method: This research uses a qualitative approach with a historical-critical study design. Data sources come from education policy documents, historical archives, and relevant secondary literature. The population in this research is all Islamic education policies during the Old Order and New Order, with samples in the form of documents and representative policies selected purposively. The research instrument is a document review guide and the analysis technique uses a content analysis approach to the socio-political dynamics of Islamic education. Results and Discussion: This study found that Islamic education during the Old Order showed resistance to the penetration of state ideology, while during the New Order there was a process of structural adaptation for the sustainability of Islamic education institutions. This finding shows a shift in the strategy of Islamic education actors in responding to power pressures. The results of this study fill the historical gap related to the relationship between the state and Islamic education, which has not been studied from a critical socio-political perspective. Conclusions and Implications: Islamic education shows flexibility between resistance and adaptation in the face of state control. This result implies the importance of understanding Islamic education not only as a religious institution, but also as a political and social arena that actively shapes national identity.